System Thinking Approach to Fish Export Determinants in the Sustainable Blue Economy - Sarasi, Vita; Yulianti, Dina; Saefulhadjar, Deny; Abdurahman, Oman; Aswandari, Desi (Research Synergy Foundation, 2025)
Wakatobi holds considerable potential in the sustainable blue economy, particularly in the fisheries sector. However, only 6.4% of its annual capture fisheries potential has been utilized, despite recent export milestones. This study employed a qualitative methodology using a systems thinking approach to explore the key determinants influencing fish exports in Wakatobi. Data were collected through in-depth interviews, focus group discussions, and secondary sources, and were analyzed using causal loop diagrams (CLD) to map systemic interactions and identify leverage points. The findings revealed that outdated port infrastructure, insufficient cold storage, limited transportation access, and inadequate post-harvest handling were the main barriers to export readiness. Additionally, gaps in policy coordination and fisher training contributed to poor fish quality and limited market access. The study concluded that addressing these interconnected issues through integrated policies, investment in cold chain infrastructure, and capacity-building initiatives is critical for improving the competitiveness of Wakatobi’s fishery exports. This research offers a systemic perspective for designing sustainable interventions that align economic growth with ecological preservation.